Individually unique body color patterns in octopus (Wunderpus photogenicus) allow for photoidentification. - Christine L Huffard; Roy L Caldwell; Ned DeLoach; David Wayne Gentry; Paul Humann; Bill MacDonald; Bruce Moore; Richard Ross; Takako Uno; Stephen Wong (PLoS ONE, 2008)
Studies on the longevity and migration patterns of wild animals rely heavily on the ability to track individual adults. Non-extractive sampling methods are particularly important when monitoring animals that are commercially important to ecotourism, and/or are rare. The use of unique body patterns to recognize and track individual vertebrates is well-established, but not common in ecological studies of invertebrates. Here we provide a method for identifying individual Wunderpus photogenicus using unique body color patterns. This charismatic tropical octopus is commercially important to the underwater photography, dive tourism, and home aquarium trades, but is yet to be monitored in the wild. Among the adults examined closely, the configurations of fixed white markings on the dorsal mantle were found to be unique. In two animals kept in aquaria, these fixed markings were found not to change over time. We believe another individual was photographed twice in the wild, two months apart. When presented with multiple images of W. photogenicus, volunteer observers reliably matched photographs of the same individuals. Given the popularity of W. photogenicus among underwater photographers, and the ease with which volunteers can correctly identify individuals, photo-identification appears to be a practical means to monitor individuals in the wild.